2007
DOI: 10.4269/ajtmh.2007.77.102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Trypanosoma cruzi Lineages and Levels of Parasitic DNA in Infected Mothers and Their Newborns

Abstract: Abstract. To better understand the factors involved in maternal-fetal transmission of Trypanosoma cruzi, we compared DNA levels-obtained by use of quantitative real-time PCR and parasitic genotypes determined by PCR amplification followed by hybridization-in Bolivian mothers and their congenitally infected newborns. Mothers and their neonates displayed markedly different parasitic DNA levels, as most maternal estimated parasitemias (> 90%) were < 10 parasites/mL, whereas those of 76% of their newborns were > 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 14 publications
6
57
2
6
Order By: Relevance
“…The parasite loads in women who transmitted infection, while higher than in nonpregnant adults with chronic T. cruzi infection, were substantially lower than those seen in the acute phase (eg, in congenitally infected infants) or in patients with human immunodeficiency virus (HIV) coinfection and T. cruzi reactivation [4,5]. HIV coinfection is also very unlikely to explain our findings.…”
contrasting
confidence: 46%
“…The parasite loads in women who transmitted infection, while higher than in nonpregnant adults with chronic T. cruzi infection, were substantially lower than those seen in the acute phase (eg, in congenitally infected infants) or in patients with human immunodeficiency virus (HIV) coinfection and T. cruzi reactivation [4,5]. HIV coinfection is also very unlikely to explain our findings.…”
contrasting
confidence: 46%
“…The DTU TcV has been reported in 80-100% of congenital cases in Argentina, Bolivia, Southern Brazil, Chile, and Paraguay (Virreira et al, 2006a(Virreira et al, , 2007Burgos et al, 2007;Corrales et al, 2009;Diez et al, 2010;Bisio et al, 2011;Ortiz et al, 2012;Bua et al, 2013;Garcia et al, 2014;Llewellyn et al, 2015). DTUs TcII and TcVI have been reported in neonates from Argentina, Bolivia, Brazil (Bahia state) and Chile (Virreira et al, 2006a;Burgos et al, 2007;Ortiz et al, 2012;Garcia et al, 2014), whereas TcIII has been identified in Paraguay (del Puerto et al, 2010) and TcI in some neonates from Argentina, Chile and Colombia (Pavia et al, 2009;Ortiz et al, 2012;Bua et al, 2013).…”
Section: Parasite Diversity and Human Congenital Chagas Diseasementioning
confidence: 94%
“…The same T. cruzi DTUs are generally detected in mothers and their infected newborns, as well as in congenitally infected twins or siblings born in consecutive gestations (Burgos et al, 2007;Virreira et al, 2007). However, when multi-clonal infections occur with different DTUs or DTU variants (Virreira et al, 2006a;Burgos et al, 2007;Corrales et al, 2009;Bisio et al, 2011;Ortiz et al, 2012;Garcia et al, 2014;Llewellyn et al, 2015), slight differences can be observed between clones infecting mothers and those found in congenitally infected infants, suggesting that a natural selection of transmitted parasite populations might occur (Burgos et al, 2007;Ortiz et al, 2012;Llewellyn et al, 2015), perhaps through interactions with placental cells and/or the host immune system (see Section 5).…”
Section: Parasite Diversity and Human Congenital Chagas Diseasementioning
confidence: 99%
“…Although the production of proinflammatory cytokines like IL-1b, IL-6, and TNF-a in response to T. cruzi Ags and the spontaneous release of TNF-a in uninfected infants born to T. cruzi-infected mothers (B 2 M + ) have been described, the levels of these cytokines in congenitally infected newborns are rather low (11,(13)(14)(15)(16), suggesting that the immune response might be an important factor in vertical transmission (17). By using a quantitative PCR (qPCR), we have previously demonstrated that the parasitemia of congenitally infected infants is highly variable at birth (7,18), and this fact posed the question whether T. cruzi-infected children also exhibit variable levels of chemokines and cytokines that might correlate with parasite burden and predict congenital infection. In this context, our study aimed to evaluate the chemokine and cytokine profiles in groups of congenitally infected and uninfected infants born to T. cruzi- Received for publication December 1, 2015.…”
mentioning
confidence: 99%